Tingkat pengetahuan petani dalam budidaya jahe di Kecamatan Moramo Kabupaten Konawe Selatan - I Gusti Ngurah Bagus Parwata; La Nalefo; Dasmin Sidu (Jurnal Sosio Agribisnis, 2023)
The aim of the research is to analyze the level of knowledge of farmers in jehe cultivation in Moramo District, South Konawe Regency. The research was carried out in Moramo District, South Konawe Regency in August 2021–October 2022. The population in this study was all ginger farmers, totaling 153 people. Sample determination was carried out using the simple random sampling method. Determining the number of samples used the Slovin formula to obtain a sample size of 60 farmers. The technique for collecting data on farmers' knowledge levels is carried out using the interview method, while data collection on skills levels uses observations and checklists. Research variables include: the level of farmer knowledge in ginger cultivation referring to Bloom's taxonomy. The data analysis used is qualitative descriptive analysis, and the Product Moment correlation test. The results of the research show that the level of knowledge of farmers in ginger cultivation is at a low level at the seed selection, seed sowing, land preparation, fertilization and post-harvest stages; and a high level of knowledge at the location selection/determination stage, planting stage, maintenance, pest control stage and harvest stage. The relationship between the level of farmer knowledge in ginger cultivation and the productivity of the ginger produced is in the weak correlation category. Keywords: farmer's level of knowledge; ginger cultivation; Bloom's Taxonomy